Natural resistance of rubber wood to marine borers and a preliminary note on the effect of preservative treatment - Rao K S; Balaji M; Santhakumaran I N; Srinivasan V V (Indian Journal of Natural Rubber Research, 1993)
Results of exposure tests carried out on rubber wood at 3 Indian ports (Visakhapatnam and Krishnapatnam on the east coast and Goa on the west coast) are reported. While untreated panels were tested at all the harbours, panels treated with CCA and CCB preservatives were tested at Visakhapatnam and Krishnapatnam. The results indicate the rubber wood is highly perishable in untreated condition, having been completely destroyed by marine borers in only 4-6 months. Treated panels fared well having undergone only neglible attack even after 24 months of exposure and are continuing in the field. This study indicates that rubber wood could be suitably upgraded with preservative treatment to find application even in the rigorous marine environment. Further tests are, however, necessary.
Keywords: Marine borers; Natural durability; Preservative treatment; Rubberwood